QUALIDADE DE SOLO E PRODUÇÃO DE FORRAGEIRAS HIBERNAIS SOBRESSEMEADAS EM PASTAGEM DE TIFTON 85 MANEJADAS SOB PASTEJO - Jezewski, Tiago J.; Londero, Ana L.; Bergoli, Luis M. G.; Maixner, Adriano R.; Fernandes, Sandra B. V.; Uhde, Leonir T. (Salão do Conhecimento, 2013)
Resumo